NDS27 combines the effect of curcumin lysinate and hydroxypropyl‐β‐cyclodextrin to inhibit equine PKCδ and NADPH oxidase involved in the oxidative burst of neutrophils. Issue 1 (18th November 2014) - Derochette, Sandrine; Mouithys-Mickalad, Ange; Franck, Thierry; Collienne, Simon; Ceusters, Justine; Deby-Dupont, Ginette; Neven, Philippe; Serteyn, Didier
Abstract : Polymorphonuclear neutrophils (PMNs) are involved in host defence against infections by the production of reactive oxygen species (ROS), but excessive PMN stimulation is associated with the development of inflammatory diseases. After appropriate stimuli, protein kinase C (PKC) triggers the assembly of NADPH oxidase (Nox2) which produces superoxide anion (O2 − ), from which ROS derive. The therapeutic use of polyphenols is proposed to lower ROS production by limiting Nox2 and PKC activities. The purpose of this study was to compare the antioxidant effect of NDS27 and NDS28, two water‐soluble forms of curcumin lysinate respectively complexed with hydroxypropyl‐β‐cyclodextrin (HPβCD) and γ‐cyclodextrin (γ‐CD), on the activity of Nox2 and PKCδ, involved in the Nox2 activation pathway. Our results, showed that NDS27 is the best inhibitor for Nox2 and PKCδ. This was illustrated by the combined effect of HPβCD and curcumin lysinate: HPβCD, but not γ‐CD, improved the release of curcumin lysinate and its exchange against lipid or cholesterol as demonstrated by the lipid colouration with Oil Red O, the extraction of radical lipophilic probes recorded by ESR and the HPLC measurements of curcumin. HPβCD not only solubilised and transported curcumin, but also indirectly enhanced its action on both PKC and Nox2 activities. The modulatory effect of NDS27 on the Nox2 activation pathway of neutrophils may open therapeutic perspectives for the control of pathologies with excessive inflammatory reactions. Abstract : The antioxidant effects of curcumin lysinate complexed with two cyclodextrins were compared. NDS27 is complexed with hydroxypropyl‐β‐ and NDS28 with γ‐cyclodextrin. NDS27 but not NDS28 inhibits translocation and activity of PKCδ and NADPH oxidase. NDS27 but not NDS28 improved the release of curcumin lysinate and its exchange with membrane lipids. NDS27 is a good candidate molecule to inhibit ROS production by neutrophils.